2009
DOI: 10.1136/emj.2008.057737
|View full text |Cite
|
Sign up to set email alerts
|

Door to relocation time for dislocated hip prosthesis: multicentre comparison of emergency department procedural sedation versus theatre-based general anaesthesia

Abstract: Door to relocation time for dislocated hip prosthesis: Multicentre comparison of emergency department procedural sedation versus theatre-based general anaesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
14
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 3 publications
3
14
0
Order By: Relevance
“…Other studies have been largely limited to single sites with patient numbers ranging up to only 640. Previous studies have tended to report on selected procedures rather than all procedures and on individual drugs rather than a range or combination of drugs 1–7 …”
Section: Discussionmentioning
confidence: 99%
“…Other studies have been largely limited to single sites with patient numbers ranging up to only 640. Previous studies have tended to report on selected procedures rather than all procedures and on individual drugs rather than a range or combination of drugs 1–7 …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they require a painful procedure to relocate their hip and may wait a mean of 7–11 h for relocation under theatre-based general anaesthesia in the UK 1 2. In contrast, early relocation in the ED promptly relieves the discomfort and periprosthetic tissue distortion.…”
mentioning
confidence: 99%
“…A retrospective chart review of 165 patients found that success rates varied from 64% (95% confidence interval 55% to 73%) with midazolam to 96% (77% to 100%) with propofol. 10 In a prospective cohort of 98 adult patients presenting with a dislocated hip prosthesis, a success rate of 96% (90% to 0.99%) was achieved using intravenous morphine and propofol. 11 A prospective randomised comparison of 214 emergency department patients found that, as well as being equally safe, procedural success rates were similar for etomidate (89%; 81% to 93%) and propofol (97%, 92% to 99%).…”
Section: How Well Do Sedative Agents Work?mentioning
confidence: 99%